Bifunctional Magnetic Luminescent Particles Based on Iron Oxide Nanoparticles Grafted with a Europium Silylated Bypiridine Tris(β-diketonate) Complex - Silva, Robson R. [UNESP]; Duarte, Adriana P.; Sábio, Rafael M. [UNESP]; Caiut, José M. A.; Gressier, Marie; Menu, Marie-Joëlle; Franco, Adolfo; Ribeiro, Sidney J. L. [UNESP] (Wiley, 2016)
A new highly magnetic-luminescent nanocomposites has been synthesized by grafting luminescent europium complex comprising tris(b-diketone) and bypridine ligand modified with a silylil function group (Eu[(TTA)3(Bpy-Si)] complex) on the surface of superparamagnetic iron oxide nanoparticles with 11 nm in size coated with a thin silica outer layer. The γ-Fe2O3/SiO2 nanoparticles were fully characterized by ATR-FTIR, FE-SEM, HR-TEM and magnetic measurements to confirm the structure of nanocomposite and the superparamagnetic behavior. Grafting with europium silylated bypiridine tris(β-diketonate) complex on nanoparticles surface was achieved by covalent bonding through triethoxysilyl groups which allows high concentration of the luminescent species. The resulting nanocomposite display superparamagnetic profile and the indirect excitation in the ultraviolet region outcomes high red luminescence intensity (at 613 nm) with narrow characteristic emission lines of Eu(III) and emission lifetime in the millisecond range. The nanocomposite is potentially useful for applications as biolabelling, imaging, bio-separation and bioassays.
Keywords: luminescent; maghemite; silylated; superparamagnetic; β-diketone